Network pharmacological insight into traditional bone healing practices of Sikkim, India - Mukunda Anuj Sharma; Bharat Gopalrao Somkuwar; Parvin A. Barbhuiya; Bhumika Gurung; Madhusmita Mahapatra; Firdous Fatima; Teresa Ningthoujam; Ashika Bhattarai; Bikash Rai; Pravin Kumar; Bishal Tiwari; Sancha Kumar Subba; et al. (PLoS ONE, 2026)
Ethnopharmacological relevance Sikkim is a mountainous state situated in the Eastern Himalaya region of India, which constitutes an area with rich cultural diversity, having different traditional healthcare practices and rituals. Traditional formulations for treating bone fractures are prevalent in rural areas of Sikkim. Aim The present study was designed to document and analyse the traditional knowledge, practices, and medicinal plants used by traditional healers of Sikkim for the treatment of Bone fractures. And network pharmacological perspectives on the bone-mending properties of the medicinal plants used by the traditional healers of Sikkim. Method Semi-structured questionnaires, semi-structured interviews, and guided field walks were used in this explorative study for four years in all six districts of Sikkim, India. The quantity indices frequency of citation (FoC) and Relative Frequency of Citation (RFC) are used to authenticate the most important medicinal plant species. Further, to examine the intricate relationships among drugs, targets, and diseases, we conducted network pharmacological annotations using several advanced tools, including Swiss Target Prediction, STRING, STITCH, DAVID, GeneCodis, and SwissADME. Results The study documented 18 distinct traditional polyherbal formulations that incorporate 32 medicinal plant species native to Sikkim and are utilised for the therapeutic management of bone fractures. Notably, several plant species identified in this investigation, particularly those exhibiting high Frequency of Citation (FoC) values, represent promising candidates for further pharmacological evaluation targeting osteoregenerative properties. Additionally, four plant species, Urtica parviflora Roxb . , Saurauia napaulensis DC., Rubus calycinus Wall. ex D.Don, and Schima wallichii (DC.) Korth., employed by traditional healers in this study, warrant prioritised phytochemical investigation due to their limited scientific exploration in existing literature. The network pharmacological annotations revealed several pathways that are directly or indirectly affecting bone development, biomineralisation, calcium signalling, endochondral ossification with skeletal dysplasia, RANK signalling, RUNX2 regulation, and Vitamin D-sensitive Ca signalling. Conclusion This study systematically documents traditional treatments for bone fractures in Sikkim, highlighting 32 medicinal plants with therapeutic potential. The findings of this study will provide baseline data to address an immediate need to preserve and scientifically validate (in vivo and in vitro) indigenous ethnomedicinal knowledge. Furthermore, provide valuable insights into the development of safe and effective lead compounds by considering the biological processes, molecular functions, and cellular components involved in bone mending from natural formulations.